98.2k views
0 votes
Solve showing steps. Use Insert equation to get the symbol and Ctrl with . For exponents x2 + 3x - 4 = 0 9x2 + 12x + 4 =0 (leave answer as a fraction) x2 - 2x - 3 = 0 x2 - 6x + 9 = 0 2x2 - 4x - 3 = 0 (round to two decimal places)*

1 Answer

4 votes

Here all the given equations are in the form of


ax^2+bx+c=0

The value of
x can be determined by the perfect square method as follows:


ax^2+bx+c=0


\Rightarrow x^2+(b)/(a)+(c)/(a)=0


\Rightarrow x^2+2*(b)/(2a)+\left((b)/(2a)\right)^2-\left((b)/(2a)\right)^2+(c)/(a)=0


\Rightarrow \left(x+(b)/(2a)\right)^2=\left((b)/(2a)\right)^2-(c)/(a)


\Rightarrow x=(-b\pm√(b^2-4ac))/(2a)\;\cdots(i)

Now, for
x^2+3x-4=0


a=1, b=3, c=-4

So, from equation (i)


x=(-3\pm√(3^2-4*1*(-4)))/(2*1)


\Rightarrow x=(3\pm√(9+16))/(2)


\Rightarrow x=(3\pm5)/(2)


\Rightarrow x=(3+5)/(2),(3-5)/(2)


\Rightarrow x= 4, -1

Similarly, for
9x^2+12x+4=0


a=9, b=12, c=4

So, from equation (i)


x=(-12\pm√(12^2-4*9*4))/(2*9)


\Rightarrow x=(-12\pm0)/(18)


\Rightarrow x=(-2)/(3)

For
x^2-2x-3=0


a=1, b=-2, c=-3


x=(-(-2)\pm√((-2)^2-4*1*(-3)))/(2*1)


\Rightarrow x=(2\pm√(16))/(2)


\Rightarrow x=(2\pm4)/(2)


\Rightarrow x=(6)/(2),(-2)/(2)


\Rightarrow x=3.00, -1.00

For
x^2-6x+9=0


a=1, b=-6, c=9


x=(-(-6)\pm√((-6)^2-4*1*9))/(2*1)


\Rightarrow x=(6\pm0)/(2)


\Rightarrow x=3.00

For
2x^2-4x-3=0


a=2, b=-4, c=-3


x=(-(-4)\pm√((-4)^2-4*2*(-3)))/(2*2)


\Rightarrow x=(4\pm√(40))/(4)


\Rightarrow x=(4\pm2√(10))/(4)


\Rightarrow x=(4+2√(10))/(4),(4-2√(10))/(4)


\Rightarrow x=2.58, -0.58

User JohnIdol
by
5.1k points